2022
DOI: 10.1111/jpm.12836
|View full text |Cite
|
Sign up to set email alerts
|

Experience of adolescents in mental health inpatient units: A metasynthesis of qualitative evidence

Abstract: What is known on the subject?• Inpatient treatment is often necessary due to the vulnerability of adolescents' mental health, and hospitalization rates are increasing.• There are both positive and negative experiences related to adolescent inpatient treatment. What does this paper add to existing knowledge?• Inpatient ward environment and interactions with staff and peers are critical in adolescents' nursing care while undergoing inpatient treatment.• Adolescents want their voice to be reflected in the treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Hong et al ( 13 ) and Choi et al ( 13 , 14 ) analyzed the long-term results of living donor liver transplantation using the big data of Korea’s national health insurance and concluded that liver donors have increased long-term mortality risk compared to similar control groups without contraindications to be organ donors, the leading cause of mortality being suicide. The impact of donation on the lives of minors as donors has not been appropriately analyzed, although previous studies using big data showed that physical changes or psychological pain for minors would be significant and that minors may have more difficulty maintaining their mental and physical health ( 20 ). Nevertheless, medical personnel (79.1% of Meds) do not expect the possibility of the death of live donors and more than half of Meds (56.1%) do not expect the possibility of the death of recipients.…”
Section: Discussionmentioning
confidence: 99%
“…Hong et al ( 13 ) and Choi et al ( 13 , 14 ) analyzed the long-term results of living donor liver transplantation using the big data of Korea’s national health insurance and concluded that liver donors have increased long-term mortality risk compared to similar control groups without contraindications to be organ donors, the leading cause of mortality being suicide. The impact of donation on the lives of minors as donors has not been appropriately analyzed, although previous studies using big data showed that physical changes or psychological pain for minors would be significant and that minors may have more difficulty maintaining their mental and physical health ( 20 ). Nevertheless, medical personnel (79.1% of Meds) do not expect the possibility of the death of live donors and more than half of Meds (56.1%) do not expect the possibility of the death of recipients.…”
Section: Discussionmentioning
confidence: 99%
“…These studies have been mostly limited to medical students and interns, with few studies focusing on resident doctors. [7][8][9][10] Given limited data over healthcare professionals, especially in nursing services from India and growing mental health problems in the medical fraternity, there is a need to assess mental health issues. Improving the understanding of mental health issues can help in amending the policies.…”
Section: Introductionmentioning
confidence: 99%